New surgical approach of retrorectal cystic hamartoma using transanal minimally invasive surgery (TAMIS) - Gutiérrez,Pablo Colsa (2014)
Introduction:Tailgut cysts or cystic hamartomas are rare developmental tumors of the pre-sacral space. Their true incidence is not well known but we must think on it when we have a patient with a multicystic uncapsulated tumor at presacral space. Tailgut cysts are often asymptomatic, and in other cases present with chronic perineal pain, constipation or rectal tenesmus. They must be treated to avoid complications such as infections (perianal fistula or abscess) and malignant degenerations (usually adenocarcinoma).Case report:One patient with anal pain was diagnosed with a perianal abscess. He was operated but at the second month review a MRI revealed a multilocular lesion in the presacral suggesting the presence of a retrorectal cystic hamartoma.An elective operation was performed by endoanal surgical approach using TAMIS. En bloc resection of the cyst was achieved with safe margins. The pathology result reported retrorectal cystic hamartoma. The patient was asymptomatic with no signs of recurrence in subsequent controls.Our experience, despite being based on one case, is evidence that TAMIS (Transanal Minimally Invasive Surgery) allows a minimally invasive dissection with similar benefits as the use of TEM/TEO devices.